Exploring Students' Media Choices for English Learning Outside of School - Rifki Rifadil Alghifari; Hasriani G; Fauzan Hari Sudding Sally (Journal of English Culture, Language, Literature and Education, 2026)
This study investigates the types of digital media selected by high-achieving students to support English learning beyond formal classroom settings. Employing a qualitative research design with purposive sampling, the study involved five eleventh-grade students from SMA IT Wahdah Islamiyah Makassar. Data were gathered through in-depth interviews and supporting documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results reveal that students predominantly utilize platforms such as YouTube, TikTok, Apple Music, and Komiku as supplementary learning resources. These media contribute significantly to the development of vocabulary, pronunciation, listening, and reading skills by providing authentic, engaging, and easily accessible English content. Students favor these platforms due to their flexibility, allowing self-paced learning that aligns with individual interests and learning preferences. Additionally, interactive features such as comment sections, duets, and content sharing foster greater motivation, confidence, and willingness to use English in real-life contexts. Nevertheless, the study also identifies several challenges, including potential distractions, unstable internet connectivity, limited application features, and difficulties in maintaining learning discipline. Despite these constraints, the findings suggest that digital media plays a meaningful role in facilitating enjoyable, autonomous, and effective English learning outside school environments.